Psychological Capital and Entrepreneurship Sustainability - Tang, Jun-Jun (Frontiers in Psychology, 2020)
Successful formation of a new venture is not the most critical indicator of the real success of an entrepreneurial venture. Instead, the sustainability of an entrepreneurial venture (i.e., entrepreneurial sustainability) is the most critical but the most difficulty goal. Entrepreneurial sustainability relies largely on positive collective psychology. This article offers systematic and detailed discussion of the effects of psychological capital on the critical elements of entrepreneurship sustainability – not just that on a successful formation of a new venture. The goal is to shed light on potential practical designs and theoretical improvement in the future.